A review of the application of ergonomics in instructional design. - Gruber, Crislaine; Vergara, Lizandra Garcia Lupi; Gontijo, Leila Amaral (Work, 2019)
BACKGROUND: Ergonomics can help instructional designers to develop projects compatible with students' needs, capabilities, and limitations. OBJECTIVE: We intend to verify the application of ergonomics in instructional design methods, methodologies, techniques, and recommendations. METHODS: We searched journal articles in the following databases: Compendex, ScienceDirect, Scopus, and Web of Science. Based on two inclusion criteria: (1) whether the article presents methods, methodologies, techniques, or recommendations for the instructional design; (2) whether the article addresses issues of ergonomics, we found 17 studies published from 1988 to 2013 in 16 journals. RESULTS: The main ergonomic concept addressed in the reviewed studies was usability, followed by accessibility, and user-centred design. Most articles suggest guidelines for embedding ergonomics in instructional design. CONCLUSIONS: We found that future research could explore topics, such as user experience, design thinking, service design, and organisational ergonomics to improve instructional design practice. The number of studies found in this review demonstrates that scientific research should explore the application of ergonomics in instructional design methods.